Transport service ontology and its application in the field of semantic search - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Transport is a crucial component in logistics, which joints each activity in the logistics chain. The performance of logistics heavily relies on the efficiency of transport services. However, until now there has not been a clear definition about transport services. Moreover, along with the rapid rise of fuel prices, the input-output ratio of transport has been trapped in an unreasonable situation, which causes the poor performance of logistics. Therefore, the research on transport service and transport service efficiency is urgently required. In this paper, we propose to use semantic web technologies to construct a conceptual model of transport services and thus present a clear structure of the transport service hierarchy. Furthermore, we propose a semantic search engine based on this transport service ontology, in order to provide an efficient tool for users to query transport service providers. This design can also be seen as a potentially alternative approach for solving the issue of transport service inefficiency.